Transformasi Digital Perguruan Tinggi: Perbandingan E-Learning dan Pembelajaran Konvensional - Ardhiyani, Raysa Puteri (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2025)
Digital transformation in higher education has become an urgent necessity in adapting to the demands of modern learning. This study compares the effectiveness of computer-based e-learning and conventional teaching methods in an Information Technology course, while also examining the role of e-learning in the digital transformation of universities. A comparative quantitative method was applied to two second-semester student groups, combined with a systematic literature review on digital education policies and practices. Results indicate no statistically significant difference in learning outcomes between the two groups. However, students in the e-learning class demonstrated greater learning independence, while those in the conventional class were more engaged in faceto-face interactions. The study also highlights the importance of technological infrastructure readiness, digital competence among faculty and students, and effective organizational change management for successful elearning implementation. These findings support blended learning as an ideal model, combining the flexibility of online learning with the interpersonal strengths of in-person teaching. The study recommends that higher education institutions develop a sustainable digital transformation roadmap and balance investments between technological tools and human capital development.